2007
DOI: 10.1111/j.1439-0442.2007.00977.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte Proliferation to Collagen Type I in Dogs

Abstract: Summary The objective of this study was to investigate if cellular reactivity to collagen type I exists in dogs with unilateral cranial cruciate ligament (CrCL) rupture and if it relates to disease progression. The patient group consisted of 10 dogs with unilateral CrCL rupture. The control dogs consisted of three healthy control dogs, and two healthy dogs with unilateral sham operations of the stifle joint. All dogs were assayed repeatedly every 6 months for 12–24 months. Peripheral blood mononuclear cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…In a recent study lymphocyte reactivity to collagen type I was assessed in dogs with cruciate disease by culturing peripheral blood mononuclear cells with human collagen type I, and was compared to sham operated and normal dogs. This study demonstrated that lymphocyte reactivity to collagen type I does occur in dogs with CrCL rupture, however, some of the sham operated dogs and healthy dogs tested positive as well (de Bruin et al, 2007b). In addition, PBMC proliferation to collagen type I was very diverse in dogs that sustained a CrCL rupture in the contralateral stifle joint, suggesting that collagen reactive T cells do not play a primary role in CrCL disease.…”
Section: Cell-mediated Immune Response In Cruciate Diseasementioning
confidence: 88%
“…In a recent study lymphocyte reactivity to collagen type I was assessed in dogs with cruciate disease by culturing peripheral blood mononuclear cells with human collagen type I, and was compared to sham operated and normal dogs. This study demonstrated that lymphocyte reactivity to collagen type I does occur in dogs with CrCL rupture, however, some of the sham operated dogs and healthy dogs tested positive as well (de Bruin et al, 2007b). In addition, PBMC proliferation to collagen type I was very diverse in dogs that sustained a CrCL rupture in the contralateral stifle joint, suggesting that collagen reactive T cells do not play a primary role in CrCL disease.…”
Section: Cell-mediated Immune Response In Cruciate Diseasementioning
confidence: 88%
“…The identity of the antigenic trigger for lymphocytic synovitis within the stifle of dogs with CCLR is unclear. Several studies have explored the hypothesis that neoepitopes of type I and type II collagen may be the immunologic trigger 6,46,47 . We have hypothesized that bacterial material may act as an antigenic trigger in this condition.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored the hypothesis that neoepitopes of type I and type II collagen may be the immunologic trigger. 6,46,47 We have hypothesized that bacterial material may act as an antigenic trigger in this condition. Translocation of bacterial material to the stifle joint is common in this arthropathy, 48 but further work is needed to determine whether a cause-effect relationship exists.…”
Section: Discussionmentioning
confidence: 99%
“…At the present time, there are two hypotheses regarding the mechanism that leads to development of inflammatory stifle arthritis and eventual CrCLR: (1) cruciate fiber rupture is a consequence of a primary synovitis [8], and (2) intrinsic and extrinsic factors induce fiber rupture, with subsequent induction of synovitis by ligament matrix neoepitopes [19][21]. The immunologic trigger for synovitis for the first hypothesis is not known, although the presence of bacterial material within the stifle has been associated with the condition [22][24].…”
Section: Introductionmentioning
confidence: 99%